A proteomic characterization shows differences in the milk fat globule membrane of buffalo and bovine milk. (September 2017) - Nguyen, Hanh T.H.; Ong, Lydia; Hoque, Ashfaqul; Kentish, Sandra E.; Williamson, Nicholas; Ang, Ching-Seng; Gras, Sally L.
Abstract: The proteins of the milk fat globule membrane (MFGM) have a number of functions, such as the regulation of milk fat secretion and metabolism, the uptake and transportation of fatty acids in the intestine, and potential protection from bacterial or viral infection. While the proteome of the MFGM in bovine milk has been extensively characterized, knowledge of these proteins in buffalo milk is limited. In this study, a proteomic approach was used to characterize the proteome of the buffalo MFGM. Multiple extraction techniques were used to increase the number of proteins identified, while label free relative quantitative liquid chromatography tandem mass spectrometry was used for comparison between the buffalo and bovine MFGM proteomes. A total of 220 buffalo MFGM proteins and 234 bovine MFGM proteins were identified after being filtered from the initial dataset of 757 and 680 proteins, respectively. A sixfold higher concentration of xanthine oxidoreductase was identified per mass of buffalo MFGM protein extracted, together with significantly greater concentrations of platelet glycoprotein 4, heat shock cognate and calcineurin B homologous protein. The expression of xanthine oxidoreductase in the MFGM of buffalo milk, which can affect milk shelf-life and flavor, was confirmed by Western blot analysis and a heterogeneous distribution of this protein observed in situ on the surface of the MFGM. The high concentration of fat in buffalo milk, together with the differences in the MFGM proteome provide insights into the differences in nutritional profile, biological function and properties of these two milk products.